2008
DOI: 10.1177/1090198107304388
|View full text |Cite
|
Sign up to set email alerts
|

Is the Receptivity of Substance Abuse Prevention Programming Affected by Students' Perceptions of the Instructor?

Abstract: Drawing on the elaboration likelihood model of persuasive communication, the authors examine the impact of the perceptions of the instructor or source on students' receptivity to a new substance abuse prevention curriculum. Using survey data from a cohort of students participating in the Adolescent Substance Abuse Prevention Study, the authors use structural equation modeling to determine the effects of the perceptions students have of their program instructor on measures of the targeted program mediators and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…ELM proposes that information that is perceived to be personally relevant and expressed by a reliable sender increases perceived acceptability [32], which has also found empirical support [33]. A review on the main aspects of computer-tailored health interventions showed that tailoring was typically achieved through giving tailored feedback, personalization, and matching content with different groups of users [34].…”
Section: Discussionmentioning
confidence: 99%
“…ELM proposes that information that is perceived to be personally relevant and expressed by a reliable sender increases perceived acceptability [32], which has also found empirical support [33]. A review on the main aspects of computer-tailored health interventions showed that tailoring was typically achieved through giving tailored feedback, personalization, and matching content with different groups of users [34].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, I think drugs are bad’[84], p. 725). Central processing of intervention content, while effortful, is deemed more likely to promote enduring behaviour change than persuasion for peripheral reasons [85] that is likely to promote transient and, consequently, unstable changes in beliefs.…”
Section: Theories Of Behaviour Changementioning
confidence: 99%
“…Stephens et al . [85] used the ELM to investigate how perceptions of the instructor might influence students' receptivity to a substance abuse prevention curriculum. Consistent with the idea of relatively peripheral processing of the information, perceptions of the instructor (e.g.…”
Section: Theories Of Behaviour Changementioning
confidence: 99%
“…Therefore, Hypothesis 6 is also supported. The affirmation of Hypotheses 5 and 6 is theoretically important because these hypotheses lend strong support to personal receptivity theory, in which people who directly experience the life courses and issues would have a stronger conversance with and impression of the experience than indirect observers (Stephens et al, 2009). Methodologically, these results suggest that the appropriateness of informants is more important than the number or diversity of the informants when conducting family research (De Los Reyes et al, 2013).…”
Section: Discussionmentioning
confidence: 64%
“…Recent research proposed to use a multi-informant approach in assessing family functioning to reduce method variance and response bias (Burt et al, 2006;Simons, Simons, & Conger, 2004), which when applied to this study incorporates the ratings of both parent and child participants about the family to test the relationships between parents' religious involvement, family socialization, and children's mental distress. According to personal receptivity theory, a life event may leave a stronger impression on those who experience it first-hand than those who observe it from a distance (Stephens et al, 2009). In this case, when family socialization is rated by only parent participants, the effect of religiosity on family socialization becomes stronger than when rated by child participants.…”
Section: Methods Variance In Family Socialization Effects By Differentmentioning
confidence: 96%